Sports dermatology: Skin disease in athletes - Carr, P. C.; Cropley, T. G. (Clinics in Sports Medicine, 2019)
There are numerous disorders of the skin that occur in athletes. These include infections, mechanical injury, and inflammatory skin diseases such as dermatitis, urticaria, and others. This paper discusses some of the most common athletic skin diseases.